The Comparative Study of the Effect of Stabilization Exercise and Stretching-Strengthening Exercise on Balance Parameters in Forward Head Posture Patients - Solmaz Salehi; Rozita Hedayati; Amir Houshang Bakhtiari; Mohamad ali sanjari; Raheb Ghorbani (Journal of Rehabilitation, 2013)
Objective: Balance disturbance is one of the observed impairments in patient with forward head posture (FHP). The aim of this study was comparing the effect of stabilization and stretching-strengthening exercises on the improvement of balance in these patients.